2020
DOI: 10.1016/j.dci.2020.103715
|View full text |Cite
|
Sign up to set email alerts
|

Rainbow trout mount a robust specific immune response upon anal administration of thymus-independent antigens

Abstract: Despite the strong demand for orally-delivered fish vaccines and the deficient response of those currently available in the market, little is known about how teleost B cells differentiate to antibody secreting cells (ASCs) in response to antigens delivered to the intestinal mucosa. To fill this gap, in the current study, we have studied the dynamics of B cell differentiation in spleen and kidney of rainbow trout ( Oncorhynchus mykiss ) anally immunized with antigens catalogued in mammals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Recently, the anal administration of thymus-independent (TI) antigens without additional adjuvants was investigated in rainbow trout. An efficient B-cell response was induced, which facilitated the production of specific IgM in serum and the differentiation of antigen-specific ASCs ( 122 ).…”
Section: Immunoglobulin Responses Following Mucosal Immunizationmentioning
confidence: 99%
“…Recently, the anal administration of thymus-independent (TI) antigens without additional adjuvants was investigated in rainbow trout. An efficient B-cell response was induced, which facilitated the production of specific IgM in serum and the differentiation of antigen-specific ASCs ( 122 ).…”
Section: Immunoglobulin Responses Following Mucosal Immunizationmentioning
confidence: 99%
“…Some studies have explored the effects of anal immunization. Although this immunization strategy offers many disadvantages from a practical point of view, it can be considered as a way to investigate how the intestinal mucosa directly reacts to antigens without having to protect the antigen from degradation in the upper digestive segments ( 86 , 87 ). In 2000, a study addressed how rainbow trout responded to fluorescein isothiocyanate (FITC) conjugated to keyhole limpet hemocyanin (KLH) when was administered intraperitoneally or anally ( 88 ).…”
Section: Local and Systemic Effects After Anal Intubationmentioning
confidence: 99%
“…The results showed that fish injected with FITC-KLH developed higher antibody level of mucosal and serum anti-FITC antibodies when compared to fish immunized anally ( 88 ). Recently, the anal route has been used to study specific B cell responses to two model antigens, TNP-KLH (2,4,6-trinitrophenyl KLH), a TD antigen and TNP-LPS, a TI antigen ( 87 ). This study demonstrated that, in the absence of additional adjuvants, rainbow trout preferentially responded to anally administered TNP-LPS, while the response to TNP-KLH was much weaker.…”
Section: Local and Systemic Effects After Anal Intubationmentioning
confidence: 99%
See 1 more Smart Citation
“…The major predicament with vaccine delivery by immersion is that practically it cannot be done in open water in ponds or cages floating in rivers and lakes. On the other hand, the major drawback with oral vaccination is that vaccines administered by ingestion are degraded in the acidic environment of the stomach/foregut before they reach the intestine where they are potentially taken up by cells of the innate immune system for local antigen presentation or transport to major immune organs (kidney/spleen) ( 45 ). There are few oral vaccines licensed to date ( 46 ), and new approaches using new technologies such as poly D, L lactic-co-glycolic acid (PLGA) nanoparticle vaccines that can protect antigens against low pH degradation in the stomach/gut are considered better alternatives.…”
Section: Disease Prevention Through Vaccinationmentioning
confidence: 99%